Whole genome sequencing and antimicrobial resistance analysis of Vibrio parahaemolyticus Vp2015094 carrying an antimicrobial-resistant plasmid. (September 2022) - Wang, Ting; Yao, Lin; Qu, Meng; Wang, Lianzhu; Li, Fengling; Tan, Zhijun; Wang, Peng; Jiang, Yanhua
Abstract: Objectives: Vibrio parahaemolyticus is an international foodborne pathogen that has caused many human infection cases. The emergence of antimicrobial resistance (AMR) in V. parahaemolyticus strains can hinder the curative effect of antimicrobials. The aim of this study was therefore to investigate the whole genome sequence of V. parahaemolyticus Vp2015094 from seafood and to explore the genetic mechanisms of AMR. Methods: The whole genome sequencing was performed using PacBio combined with Illumina platform. The antimicrobial resistance genes (ARGs) were detected by Resistance Gene Identifier in the Comprehensive Antibiotic Resistance Database. The antimicrobial-resistant plasmid of Vp2015094 was compared with other similar plasmids from different sources. Results: Vibrio parahaemolyticus Vp2015094 contained two chromosomes and two plasmids. ARGs were identified on chromosome and plasmid pVp94-1. Plasmid pVp94-1 carried tetracycline resistance genes ( tetB, tetM, tetR, tetC ), aminoglycoside resistance genes ( aph(3′')-Ib, aph(6)-Id ), sulphonamide resistance genes ( sul2 ), diaminopyrimidine resistance gene ( dfrA6 ), fluoroquinolone resistance gene ( qnrVC6 ), phenicol resistance gene ( floR ) and penam resistance gene ( bla CARB-19 ), which were surrounded by transposase genes. Plasmid pVp94-1 was a conjugative plasmid with a high transfer frequency. Conclusion: Vibrio parahaemolyticus Vp2015094 exhibited multi-antimicrobial resistance that was mediated by chromosome and plasmid. Plasmid and transposon were speculated to be responsible for the dissemination of ARGs. This study provided an understanding of the genetic mechanisms of AMR of V. parahaemolyticus from seafood, which needs continued monitoring.